Readiness for Electronic Medical Record Implementation at Simpang Kawat Public Health Center, Jambi City in 2024 - Fazira Cahayatul Rahmi; Arnild Augina Mekarisce; Rumita Ena Sari; Andy Amir; Dwi Noerjoedianto (International Journal of Health Engineering and Technology, 2026)
Human resources are the main asset that determines the success of Electronic Medical Record (EMR) implementation. This study aims to analyze the readiness for EMR implementation at Simpang Kawat Public Health Center, Jambi City in 2024 through the aspects of input, process, and output. This research used a descriptive qualitative method with in-depth interviews with informants selected purposively. Data collection techniques included interviews, observation, and documentation, with validity testing using source and method triangulation. In the input aspect, the quantity of human resources is sufficient, but routine training has not been scheduled. BOK funds are sufficient for monthly operations. Technical obstacles were found in the damaged generator. The service process is digital in accordance with PMK No. 24 of 2022. The output shows increased time efficiency and minimized data errors through the integration of NIK and BPJS. Overall, EMR implementation has been going well, but improvements are needed in supporting infrastructure, especially electricity backup, and periodic training to maintain the quality of digital services.